Carosello: mirror and social, cultural and linguistic instrument of the Italian spirit. - Giusto, Marcello (Sperimentare ed esprimere l’Italianità: Aspetti linguistici e glottodidattici, 2021)
The aim of the article “Carosello: Italianness’ mirror and social, cultural and linguistic device” is to reveal the important role of “Carosello”, the television container of promotional messages created by RAI in 1957, seen through the key of Italianness. It was an entirely Italian invention, with an innovative and original structure, which also influenced culture and society. The analysis of selected samples attempts to demonstrate how his testimonials, repeated slogans, neologism and idioms entered the common language and imaginary especially as bearers of the new consumer society’s message organised in a system of values developed around Italianness and expressed through stylistically and persuasively functional rhetorical elements.